Design and Application of TCMS Display Based on Ergonomics - HAN Shuang; LIU Zhixin; LU Yang (机车电传动)
A kind of TCMS display was designed and optimized to a certain overseas market project based on the research of vision, hearing and human habits and other fields in ergonomics. The design of the TCMS display interface was optimized on its button layout, display colors and fonts for improving the visibility, which could make the driver read the train running status quickly and precisely and perform the corresponding operation effectively, and then, the safety and reliability of TCMS and even the train could be enhanced. It was proved that the application of ergonomics in the design works of TCMS could greatly improve the visibility and functionality of the whole system.